An efficient scheme to support direct revocation in cloud computing using CPABE: The approach with less time constraints - G. Dande, Rupali; Amol D. Potgantwar, Dr; Amol D. Potgantwar, Dr (International Journal of Engineering and Technology, 2018)
Secure Data sharing is a major issue of concern in cloud computing. CPABE is well known encryption technique for dealing with the problem of data security over network. Most of the files have multilevel access hierarchy especially in health care and military domain. The hierarchy structure and revocation of shared files is not scrutinized in CP-ABE.Â  In this paper, experts proposed the enhanced method of encryption to support the direct revocation, in which sender specifies the revocation list during encryption of cipher text so that the problem of releasing periodic key update information in indirect revocation is vanished. Here the direct revocation mechanism and file access based hierarchy are merged to get enhanced CPABE. The multilevel access structure is integrated and merged with encrypted files with current access structure. Along with revocation, aim is also to improve the overall system performance with respect to encryption time and decryption time. Experimental result shows the enhanced performance of the proposed system as compared to existing system with respect to time and security constraints. Moreover the scheme is secure under the standard security assumption. Finally, based on the research, it gives forthcoming research direction to expand and implement the scheme in any practical application where security is main concern by proper coalition of the proposed technologies.Â Â